2002
DOI: 10.1038/sj.ejcn.1601386
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between an in vitro method to determine carbohydrate digestion rate and the glycemic response in young men

Abstract: Objective: This study examines the relationship between the results of in vitro determinations of carbohydrate digestion rates and the glycemic index. Subjects: Ten healthy non smoking men, aged between 21 and 24-y-old, were selected to participate in the study. Methods: Six different meals with similar lelvels of carbohydrates were assayed at breakfast in ten subjects and blood samples were obtained at 0, 15, 30, 60 and 120 min to determine glucose levels. The Englyst's enzymatic method was used in the in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 21 publications
1
32
0
4
Order By: Relevance
“…Although numerous studies have confirmed both the role that various starch sources play on in vivo GI (Parada and Aguilera, 2011) and the relationship between HI and GI for humans (Bjö rck et al, 2000;Araya et al, 2002;Garsetti et al, 2005), limited information is currently available for pigs. Furthermore, to overcome the expense and difficulty of the in vivo analysis, an in vitro prediction of the GI for pigs, based on the released glucose throughout time after an enzymatic digestion, could be considered as a promising alternative to animal trials.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have confirmed both the role that various starch sources play on in vivo GI (Parada and Aguilera, 2011) and the relationship between HI and GI for humans (Bjö rck et al, 2000;Araya et al, 2002;Garsetti et al, 2005), limited information is currently available for pigs. Furthermore, to overcome the expense and difficulty of the in vivo analysis, an in vitro prediction of the GI for pigs, based on the released glucose throughout time after an enzymatic digestion, could be considered as a promising alternative to animal trials.…”
Section: Introductionmentioning
confidence: 99%
“…The carbohydrate digestion rates were determined using the enzymatic method proposed by Englyst et al (1992), modified by extending the hydrolysis time to 180 min (very slowly digestible starch fraction) (Araya et al, 2002). The meal ingredients and the carbohydrate percentage of each of them are shown in Table 3.…”
Section: Dietsmentioning
confidence: 99%
“…Several authors have shown that food carbohydrates differ in their in vitro digestion rates (Björck & Siljestrom, 1987. Furthermore, some biological biomarkers such as glycemic and insulinemic levels are dependent on the sensibility of food carbohydrates to enzymatic digestion in the intestinal tract (Bornet et al, 1989;Englyst et al, 1999;Araya et al 2002) and a relationship between the in vitro and biological essays has been reported. Some works have demonstrated in adults and obese adolescents an inverse relationship between glycemic index and satiety (Ludwig et al, 1999;Ludwig 2000;Augustin et al, 2002), but in other's investigations the results showed the inverse tendency (Holt et al, 1996;Raben et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro starch hydrolysis has been identified as a simple inexpensive experimental method used in estimating glycemic response of carbohydrate meals (Jenkins et al, 1987;Araya et al, 2002;Dona et al, 2010). These findings helped in reducing the use of human beings and avoiding the complexities associated with human management involved in in vivo experimental designs.…”
Section: Introductionmentioning
confidence: 99%